The paradox of clopidogrel use in patients with acute coronary syndromes and diabetes: insight from the Diabetes and Acute Coronary Syndrome Registry. Issue 4 (June 2018) - Ferlini, Marco; Musumeci, Giuseppe; Grieco, Niccolò; Rossini, Roberta; De Servi, Stefano; Mafrici, Antonio; Sponzilli, Carlo; Demarchi, Andrea; Assanelli, Emilio M.; Camisasca, Paola; Chizzola, Giuliano; Corrada, Elena; et al.
Abstract : Background: Patients with diabetes mellitus (DM) and acute coronary syndromes have a greater level of platelet aggregation and a poor response to oral antiplatelet drugs. Clopidogrel is still widely used in clinical practice, despite the current evidence favoring ticagrelor and prasugrel. Aim: The aim of this study was to investigate the determinants of clopidogrel use in the population of the multicenter prospective 'Acute Coronary Syndrome and Diabetes Registry' carried out during a 9-week period between March and May 2015 at 29 Hospitals. Patients and methods: A total of 559 consecutive acute coronary syndrome patients [mean age: 68.7±11.3 years, 50% ST-elevation myocardial infarction (STEMI)], with 'known DM' (56%) or 'hyperglycemia' at admission, were included in the registry; 460 (85%) patients received a myocardial revascularization. Results: At hospital discharge, dual antiplatelet therapy was prescribed to 88% of the patients (clopidogrel ticagrelor and prasugrel to 39, 38, and 23%, respectively). Differences in P2Y12 inhibitor administration were recorded on the basis of history of diabetes, age, and clinical presentation (unstable angina/non-STEMI vs. non-STEMI). On univariate analysis, age older than 75 years or more, known DM, peripheral artery disease, previous myocardial infarction, previous revascularization, complete revascularization, previous cerebrovascular event, creatinine clearance, unstable angina/non-STEMI at presentation, Global Registry of Acute Coronary Events Score, EuroSCORE, CRUSADE Bleeding Score, and oral anticoagulant therapy were significantly associated with clopidogrel choice at discharge. On multivariate analysis, only oral anticoagulant therapy and the CRUSADE Bleeding Score remained independent predictors of clopidogrel prescription. Conclusion: In the present registry of a high-risk population, clopidogrel was the most used P2Y12 inhibitor at hospital discharge, confirming the 'paradox' to treat sicker patients with the less effective drug. Diabetic status, a marker of higher thrombotic risk, did not influence this choice; however, bleeding risk was taken into account.